Small molecule activation by constrained phosphorus compounds: insights from theory - Pal, Amrita; Vanka, Kumar (Inorganic Chemistry, 2016)
An exciting new development in main group chemistry has been the use of a constrained, flat, phosphorus-based complex to mediate in reactions such as the dehydrogenation of ammonia borane (AB), and the activation of the NH bond in primary amines. Its importance is based on the fact that it shows that main group compounds, when properly designed, can be as effective as transition metal complexes for doing significant chemical transformations. What the current computational study, employing density functional theory (DFT), reveals is that a common, general mechanism exists that accounts for the behavior of the flat phosphorus compound in the different reactions that have been experimentally reported to date. This mechanism, which involves the mediation by a base as a proton transfer agent, is simpler and energetically more favorable than the previous mechanisms that have been proposed for the same reactions in the literature. It is likely that the knowledge gained from the current work about the chemical behavior of this phosphorus compound can be utilized to design new constrained phosphorus-based compounds.